PERUBAHAN DAN KEBERLANJUTAN TARI BALANSE MADAM DI LINGKUNGAN MASYARAKAT NIAS PADANG - Novina Yeni Fatrina; Yan Stevenson (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
The article entitled “The Change and Sustainability of Balanse Madam Dance in the Nias Padang Community” aims to reveal Balanse Madam dance changes and to analyze the sustainability. After many of his supporting artists died, many changes occurred in Balanse Madam dance, both in terms of dancers as well as the music of the accompaniment.Qualitative description research method with the approach of interaction and interpretation analysis was used to reveal the problem. The tracking is done by viewing and analyzing Balanse Madam dance changes on the development of forming elements in dance compositions from 1995 to present. The study of change and sustainability of Balanse Madam dance in Nias Padang society was analyzed by using culture endurance theory proposed by Edi Sedyawati and the theory of composition forming elements used by R.M. Soedarsono.The study results showed that over time, various things affect the condition of Balanse Madam dance, resulting in changes in some elements of Balanse Madam dance formation. The changes are (1) the dancers, who used to be housewives, can now be performed by the dancers that are still teenagers; (2) music accompaniment, used to be played directly by musicians, but now can be accompanied by music recordings. The use of teen dancer and music recordingarea form of sustainability of Balanse Madam dance.